Establishing a community infusion service in Canterbury, New Zealand: strategies and lessons - Graham McGeoch; Brett Shand; Lisa McGonigle (CSIRO Publishing, 2022)
Background and context An increasing number of drugs and blood products need to be delivered by intravenous infusion. In the Canterbury region of New Zealand, these have historically been delivered at a hospital site; however, some infusions could be delivered in a community setting without compromising patient safety. Assessment of problem The Canterbury health system has a key strategic objective of delivering care close to patients' homes. In 2018, Canterbury district health board (DHB) put out a tender for a community infusion service that would deliver blood products and other intravenous drugs with appropriate medical oversight. Strategies for improvement Following an interview and selection process, a fee-for-service contract was developed with a group of general practices with partial common ownership. It was nurse-led with medical oversight available. In July 2018, a Community Infusion Service (CIS) was started in two urban sites in Canterbury. It later expanded to two more sites, one urban and one rural. Results From July 2018 to May 2021, over 3000 infusions and blood transfusions were delivered by the CIS across seven infusion types (blood; immunoglobulin; infliximab; natalizumab; pamidronate; toculizumab; zoledronic acid). Both general practice and hospital services referred patients to the CIS. No major incidents were reported. Patients reported satisfaction with the service. Lessons Infusions and blood products can be delivered safely nearer to patients' homes in primary care in a New Zealand setting. Medical input was rarely required; however, the transition was resource-intensive; it required both overall process and criteria negotiations, as well as individual patient discussions. In its initial stages, the CIS did not have adequate clinical governance and operational support, which affected the speed and scale of its development.